“From war to tolerance? Bottom-up and top-down approaches to (re)building interethnic ties in the areas of the former Yugoslavia” - Banovac, Boris (Array, 2014)
In recent history the Balkans passed through periods of conflict and violence typical of many post-imperial nation-states that are unable to establish lateral links with their neighbors without or outside the central (imperial) connection. In a way, these states imitated historical path of imperial conquests. In this regard, ethnic conflicts that escalated into wars of the former Yugoslavia can be taken as examples of an erratic transformation of post-imperial into modern nation-states that are eager to build up democracy at home and develop peaceful coexistence with others in international environment. Nevertheless, not all multiethnic areas were caught up in violence (e.g. instances of “peace enclaves” in multiethnic areas in Croatia, Bosnia and Heregovina and in Kosovo). Through such examples, which will be illustrated with results of empirical research, we recognize potentials for building tolerance from below. On the other hand, in most other places peace was a follow up of post-conflict processes. In these cases, local potentials of ethnic tolerance were rather weak. The paper provides some examples illustrating regional differences in this regard within Croatia. Actually, the whole process of normalization of ethnic relations in peaceful terms is far from being linear and is hardly going smoothly. Some parts of national elites foster distance and antagonism against the ”others”. On the other hand, especially following EU accession of Croatia, nationalistic rhetoric significantly receded on the level of the official politics. The question is then whether the impact of policies in institutional sphere, both national and international, i.e. top-down approach, is decisive in shaping inter-ethnic relations. The conclusion is that the institutional, top-down arrangements of peace and tolerance cannot be sustainable without concomitant bottom-up processes on micro level, which theoretically corresponds to a “conformant policy” against “linear policy” or determinism of the center and contingencies in the periphery.